Molecular Analysis of Fetal and Adult Primary Human Liver Sinusoidal Endothelial Cells: A Comparison to Other Endothelial Cells - Muhammad Ahmer Jamil (International Journal of Molecular Sciences, 2020)
In humans, Factor VIII (F8) deficiency leads to hemophilia A and F8 is largely synthesized and secreted by the liver sinusoidal endothelial cells (LSECs). However, the specificity and characteristics of these cells in comparison to other endothelial cells is not well known. In this study, we performed genome wide expression and CpG methylation profiling of fetal and adult human primary LSECs together with other fetal primary endothelial cells from lung (micro-vascular and arterial), and heart (micro-vascular). Our results reveal expression and methylation markers distinguishing LSECs at both fetal and adult stages. Differential gene expression of fetal LSECs in comparison to other fetal endothelial cells pointed to several differentially regulated pathways and biofunctions in fetal LSECs. We used targeted bisulfite resequencing to confirm selected top differentially methylated regions. We further designed an assay where we used the selected methylation markers to test the degree of similarity of in-house iPS generated vascular endothelial cells to primary LSECs; a higher similarity was found to fetal than to adult LSECs. In this study, we provide a detailed molecular profile of LSECs and a guide to testing the effectiveness of production of in vitro differentiated LSECs.